Perceived feasibility, acceptability, and cultural adaptation for a mental health intervention in rural Haiti - Zubieta, Caroline (Cult Med Psychiatry, 2020)
Mental healthcare is largely unavailable throughout Haiti, particularly in rural areas. The aim of the current study is to explore perceived feasibility, acceptability, and effectiveness of potential culturally adapted interventions to improve mental health among Haitian women. The study used focus group discussions (n=12) to explore five potential interventions to promote mental health: individual counseling, income-generating skills training, peer support groups, reproductive health education, and couples’ communication training. Findings indicate that individual counseling, support group, and skills training components were generally anticipated to be effective, acceptable, and feasible by both male and female participants. That being said, participants expressed doubts regarding the acceptability of the couples’ communication training and reproductive health education due to: a perceived lack of male interest, traditional male and female gender roles, lack of female autonomy, and misconceptions about family planning. Additionally, the feasibility, effectiveness, and acceptability of the components were described as dependent on cost, proximity to participants, and inclusion of a female health promoter that is known in the community. Given the lack of research on intervention approaches in Haiti, particularly those targeting mental health, this study provides a foundation for developing prevention and treatment approaches for mental distress among Haitian women.